2017
DOI: 10.1186/s12889-017-4319-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing national infectious disease surveillance systems: China and the Netherlands

Abstract: BackgroundRisk assessment and early warning (RAEW) are essential components of any infectious disease surveillance system. In light of the International Health Regulations (IHR)(2005), this study compares the organisation of RAEW in China and the Netherlands. The respective approaches towards surveillance of arboviral disease and unexplained pneumonia were analysed to gain a better understanding of the RAEW mode of operation. This study may be used to explore options for further strengthening of global collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…Case information is entered by all healthcare providers at all level via a nationally-standard form into a web-based Notifiable Infectious Diseases Reporting Information System (NIDRIS). In addition, a national system called China Infectious Disease Automated-alert and Response System (CIDARS) have been developed since 2005 to provide real-time outbreak notifications [ 15 , 16 ]. In term of diagnosis, the provincial branches are responsible for testing suspected human patient and animal sera, collecting infected animals and identifying infectious isolates by culture and microscopic agglutination test (MAT) according to the national diagnostic criteria for leptospirosis issued by the National Health and Family Planning Commission (NHFPC) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Case information is entered by all healthcare providers at all level via a nationally-standard form into a web-based Notifiable Infectious Diseases Reporting Information System (NIDRIS). In addition, a national system called China Infectious Disease Automated-alert and Response System (CIDARS) have been developed since 2005 to provide real-time outbreak notifications [ 15 , 16 ]. In term of diagnosis, the provincial branches are responsible for testing suspected human patient and animal sera, collecting infected animals and identifying infectious isolates by culture and microscopic agglutination test (MAT) according to the national diagnostic criteria for leptospirosis issued by the National Health and Family Planning Commission (NHFPC) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…An immediate need is educating and supporting all hospitals with microbiological facilities to report their culture-confirmed melioidosis cases and their mortalities to Report 506. A long-term solution is to automate the reporting system, similar to the systems in the Netherlands and China [ 64 ]. Another option is to have all admission and laboratory data from all hospitals in Thailand collected into one central data system.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…These systems are four-level from the national to the county and include all health care institutions across the country, allowing for the development and application of an early warning system at the county level in China (13). Some studies have compared the Chinese emergency events surveillance system with those of other countries and have found that China has a broader "all-hazard" approach, including, for example, chemical incidents (14).…”
Section: Improved Monitoring and Early Warning Systemsmentioning
confidence: 99%